PARASITISASI DAN POPULASI PARASITOID Diadegma semiclausum (HYMENOPTERA: ICHNEUMONIDAE) PADA TANAMAN BRASSICACEAE DI KECAMATAN MODOINDING KABUPATEN MINAHASA SELATAN - Herens A. Parera; Jantje Pelealu; Moulwy F. Dien; Caroulus S. Rante (Universitas Sam Ratulangi, 2014)
ABSTRACKCabbage (Brassica oleracea var. Capitata L. f. alba DC) is a vegetable that contains vitamins, minerals, proteins, carbohydrates and grese for the formation of human body and increase energy for the activity of human muscles. North Sulawesi is a region that has a large planting vegetables in the east of Indonesia. Cabbage crop harvested area of approximately 1,614 ha, with an average production of 17.25 tonnes per ha. The low production of cabbage in North Sulawesi caused by farming system which is still conventional and the presence of pests especially Plutella xylostella and Crocidolomia binotalis. The study aims to determine the percentage of the population and parasitization of the parasitoid Diadegma semiclausum in District Modoinding. The experiment was conducted in the South Minahasa Modoinding. Implementation of the study lasted for six months, start from July to December 2013, the research using survey method conducted on cabbage and other Brassicaceae plant at Modoinding District of South Minahasa Regency. Criteria for the location of the sample is the presence or type of cabbage and other Brassicaceae. Materials and tools used in this research are larvae and pupae of Plutella xylostella, Brassicaceae plants, sample bottles, bottle collection of 70% alcohol, tweezers, scissors, cutter, aqua glass, asahi cloth, rubber bands,